Bending examination of advanced generation of composite structures with specific properties exposed to different loads - Zitouni, Ahmed; Bouderba, Bachir; Dellal, Abdelkader; Berrabah, Hamza Madjid (Vojnotehnički glasnik / Military Technical Courier, 2024)
Introduction/purpose: This article presents the bending examination of advanced-generation composite structures with specific properties exposed to different loads.Methods: This paper thus proposes and introduces a new generalized five-variable shear strain theory for calculating the static response of functionally graded rectangular plates made of ceramic and metal. Notably, our theory eliminates the need for a shear correction factor and ensures zero-shear stress conditions on both the upper and lower surfaces. Numerical investigations are introduced to interpret the influences of loading conditions and variations of power of functionally graded material, modulus ratio, aspect ratio, and thickness ratio on the bending behavior of FGPs. These analyzes are then compared to the results available in the literature.Results: Preliminary results include a comparative analysis with standard higher-order shear deformation theories (PSDPT, ESDPT, SSDPT), as well as Mindlin and Kirchhoff theories (FSDPT and CPT).Conclusion: Our theory contributes alongside established theories in the field, providing valuable insights into the static thermomechanical response of functionally graded rectangular plates. This encompasses the influence of volume fraction exponent values on nondimensional displacements and stresses, the impact of aspect ratios on deflection, and the effects of the thermal field on deflection and stresses. Numerical examples of the bending examination of advanced-generation composite structures with specific properties exposed to different loads demonstrate the accuracy of the present theory.
Keywords: functionally graded materials; bending; higher-order shear deformation theories; thermomechanical